Halo phenomena observed in the region of Uppsala, Sweden, from 1974 to 1981 - Rindert, Birger (Uppsala University, 2019)
The described halo phenomena or halo components were observed during an unbroken period of 8 years. Only a small number of the observations were made in other parts of the country.

These observations are not only of interest for meteorologists but even for persons interested in optical events in the atmosphere. Worth to mention here are photographers and people interested in nature. The experience of a brilliant and comprehensive halo phenomena is something one will never forget! Most prominent are special optical events such as multiple halo or mirage. I here refer to August 21, 1974, a halo display with seven components.

I strongly recommend the following scientific article describing the types of well formed ice crystals necessary to create the observed halo components. The author of the article was one of my teachers at Uppsala University:

Liljequist, G. H. 1956. Halo-phenomena and ice-crystals. Norwegian-British-Swedish Antarctic Expedition, 1949-52: Scientific Results, Vol. II, Part 2A, Norsk Polarinstitutt, Oslo.

The dataset was originally published in DiVA and moved to SND in 2024.

De beskrivna halofenomenen eller halokomponenterna observerades under en obruten 3-årsperiod, från 1974 till 1976. Endast ett litet antal observationer utfördes i andra delar av landet.

Dessa observationer är inte bara av intresse för meteorologer utan även för personer intresserade av optiska fenomen i atmosfären. Värt att nämna är här fotografer och personer med naturintresse. Upplevelsen av ett briljant och omfattande halofenomen är någonting man aldrig kommer att glömma! Mest framträdande är speciella optiska företeelser som multipla halon eller hägringar. Jag hänvisar här till 21 augusti 1974, ett halo-skådespel med sju halo-komponenter.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Halo-fenomen observerade i Uppsalatrakten från 1974 till 1976
Keywords: halo phenomena; halofenomen; observations; observationer; halo components; halokomponenter; optical phenomena; optiska fenomen; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap